Division Construction Government Authority In Law Number 23 of 2014 - Salmon, Hendrik; Lekipiouw, Sherlock (Journal of Ecohumanism, 2024)
The concept of the division of government affairs in deconcentrating and co-administration has a long history in Indonesian constitutional records. Amendments to the 1945 Constitution, especially the second amendment concerning the concept and pattern of the division of a government, have indicated that a centralized government would actually pose a threat to disintegration so that strengthening decentralization is not a weakening of Indonesia, but an effort to strengthen it. In other words, the choice to use the concept of autonomy as broadly as possible should be understood as a way to build a just balance between central and regional power relations. One of the issues regarding the constitutionality of regional government that has become a space for academic debate after the issuance of Law No. 23 of 2014 concerning Trade Law relates to the concept of the division of government affairs between government structures. Moving on from the point of view of State Constitutional Law and State Administrative Law, the analysis will be directed at the parameters used to construct the division of authority between government structures based on executive power (Article 4 paragraph (1) of the 1945 Constitution of the Republic of Indonesia) or based on the authority stipulated by the constitution. In another part, Law Number 23 of 2014 has reduced the essence of the concept of deconcentrating which previously was only carried out by the Governor, now it is also carried out by the Regent/Mayor. In such a concept, the problem is how to juxtapose the decentralization method with other methods such as deconcentrating and co-administration and institutionalization of the three principles.